FOUNDATIONAL RULES OF GRAMMATICAL EXAMINATION (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
This article explores the fundamental principles of grammatical analysis, which is crucial for understanding and dissecting the structure of language. It covers the identification of sentence constituents (e.g., noun phrases, verb phrases), the analysis of syntactic structure, and the role of morphology in breaking down words. The piece emphasizes the importance of recognizing parts of speech and understanding grammatical relations such as subject, object, and complement.